OPTIMIZATION OF DIETARY ENERGY DENSITY FOR BROILER CHICKENS DURING THE COLD DRY SEASON OF JOS, PLATEAU STATE, NIGERIA - Idachaba, Collins Udagbene; Adeniyi, Adebayo Kunle; Oludayo, Akinsola Michael; Oladipo, Mary Foluke; Kurdor, Peter Nandur; Abdullahi, Idris; Zungum, Aliyu Garba (FUDMA Journal of Sciences, 2026)
This study evaluated the optimization of dietary energy density for broiler chickens during the cold dry season of Jos, Plateau State, Nigeria. A total of 210 Arbor Acre day-old broiler chicks were assigned to five dietary treatments in a completely randomized design with three replicates of fourteen birds each. Starter diets contained 3000, 3025, 3050, 3075 and 3100 kcal/kg ME in diets T1 to T5 respectively, with 23% CP in all diets. Finisher diets contained 3200, 3225, 3250, 3275, and 3300 kcal/kg ME in diets T1 to T5 respectively with 20% CP in all diets. Feed and water were provided ad libitum, growth indices and villi morphometry were evaluated. During the starter phase, birds fed 3075 kcal/kg ME achieved the highest (P
Keywords: Broiler; Metabolizable energy; Feed; Diets; Growth performance